PERAN PEMBIAYAAN DALAM MENINGKATKAN USAHA MIKRO PADA BANK SUMUT SYARI’AH CABANG RINGROAD MEDAN SELAYANG - Nurmala Sari; Ahmad Adib Nasution; Arifa Pratami (MUTLAQAH: Jurnal Kajian Ekonomi Syariah, 2022)
Developing micro-enterprises in Indonesia cannot be separated from banking support in disbursing financing to micro-enterprises. The role of Islamic banking in developing community businesses, especially in micro-enterprises, is to participate in providing financing to the community to develop their businesses. In this study, there are two problem formulations, namely what is the role of financing in increasing micro-enterprises at Bank Sumut Syari'ah Rongroad Medan Selayang Branch? What is the condition of the role of financing in increasing micro-enterprises before and after the existence of Bank Sumut Syari'ah Rongroad Medan Selayang Branch? And how is the role of Islamic banks in increasing micro-enterprises at Bank Sumut Syari'ah Rongroad Branch.The purpose of this study is to determine the role of financing in increasing micro-enterprises at Bank Sumut Syari'ah Rongroad Medan Selayang Branch, to determine differences in customer income before and after receiving financing, and to analyze the role of Islamic banks in increasing micro-enterprises at Bank Sumut Syari'ah. Rongroad Branch The research methodology used is a quantitative approach. The sample used is the Micro business customers of Bnak Sumut Syariah Medan Ringroad Branch in 2021 as many as 30 respondents. The data analysis used in this study is simple linear regression analysis and comparison test, with the help of SPSS version 20. The results of the research conducted indicate that financing has a significant effect on increasing microfinance business at Bank Sumut Syariah Ringroad Medan Selayang Branch. The development of the customer's business occurred in increasing business capital, increasing sales turnover, increasing income, expanding business and increasing workforce. And there is a significant difference in the level of income of PT. Sumut Syariah Medan Ringroad Branch Office before and after obtaining microfinance. The average income of customers after obtaining microfinance for North Sumatra Syariah Medan Branch Office increased by 35%. Where the average income before obtaining microfinance is Rp. 3,521,579.55 and after obtaining microfinancing is Rp. 4,752,329.55.